2022
DOI: 10.1161/jaha.121.025171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Ischemia with Nonobstructive Coronary Arteries According to Coronary Microvascular Dysfunction

Abstract: Background In the absence of obstructive coronary stenoses, abnormality of noninvasive stress tests (NIT) in patients with chronic coronary syndromes may indicate myocardial ischemia of nonobstructive coronary arteries (INOCA). The differential prognosis of INOCA according to the presence of coronary microvascular dysfunction (CMD) and incremental prognostic value of CMD with intracoronary physiologic assessment on top of NIT information remains unknown. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…In the setting of significant epicardial artery stenosis, the additional resistance from coexisting CMD further limits maximal coronary blood flow [ 135 ]. Notably, CMD, with or without vasospastic angina, is one of the major endotypes of myocardial ischemia without obstructive CAD, which, when present, results in a significantly worsened prognosis with a higher risk of major adverse CV events at 5 years [ 136 ]. In a recent retrospective cross-sectional study involving an unselected population of T2DM patients experiencing chest pain and non-obstructive CAD, 72.1% of the 129 studied diabetic patients had an endothelial-dependent or -independent CMD, which was associated with a linear increase of HbA1c amongst women but not men [ 137 ].…”
Section: Therapeutic Management Of Cmd In Diabetesmentioning
confidence: 99%
“…In the setting of significant epicardial artery stenosis, the additional resistance from coexisting CMD further limits maximal coronary blood flow [ 135 ]. Notably, CMD, with or without vasospastic angina, is one of the major endotypes of myocardial ischemia without obstructive CAD, which, when present, results in a significantly worsened prognosis with a higher risk of major adverse CV events at 5 years [ 136 ]. In a recent retrospective cross-sectional study involving an unselected population of T2DM patients experiencing chest pain and non-obstructive CAD, 72.1% of the 129 studied diabetic patients had an endothelial-dependent or -independent CMD, which was associated with a linear increase of HbA1c amongst women but not men [ 137 ].…”
Section: Therapeutic Management Of Cmd In Diabetesmentioning
confidence: 99%
“…CFR was higher in patients with <20% and 0% stenosis than in 20%–49% and 1%–40% stenosis, respectively, 18,42 both studies demonstrated the association of CFR with adverse outcomes among women with suspect ischemia 18 and patients with diabetes, 42 but these studies did not study the effect of nonobstructive stenosis on CMD. In addition, a recent study showed that angiographic coronary diameter stenosis was not associated with the presence of CMD in INOCA 43 …”
Section: Discussionmentioning
confidence: 96%
“…In addition, a recent study showed that angiographic coronary diameter stenosis was not associated with the presence of CMD in INOCA. 43 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations